2016
DOI: 10.1117/1.jbo.21.8.086008
|View full text |Cite
|
Sign up to set email alerts
|

Navigation of a robot-integrated fluorescence laparoscope in preoperative SPECT/CT and intraoperative freehand SPECT imaging data: a phantom study

Abstract: Robot-assisted laparoscopic surgery is becoming an established technique for prostatectomy and is increasingly being explored for other types of cancer. Linking intraoperative imaging techniques, such as fluorescence guidance, with the three-dimensional insights provided by preoperative imaging remains a challenge. Navigation technologies may provide a solution, especially when directly linked to both the robotic setup and the fluorescence laparoscope. We evaluated the feasibility of such a setup. Preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In this study we have investigated possible solutions to solve the interference issues found during the navigation of clinical (1) the spectral overlap between the ICG emission light and the NIR OTS light, (2) the OTS light intensity, (3) the OTS duty cycle, (4) the OTS frequency, (5) the fluorescence camera recording frequency, and (6) the camera sensitivity. As we have also observed during our previous studies, 4,5,8 this combination of features means that the severity of interference varied between the type of fluorescence camera used. More specifically, the observed interference with the OTS vicra completely obstructed fluorescence imaging with the PDE camera while its influence on the imaging output of the VITOM camera was only minor.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In this study we have investigated possible solutions to solve the interference issues found during the navigation of clinical (1) the spectral overlap between the ICG emission light and the NIR OTS light, (2) the OTS light intensity, (3) the OTS duty cycle, (4) the OTS frequency, (5) the fluorescence camera recording frequency, and (6) the camera sensitivity. As we have also observed during our previous studies, 4,5,8 this combination of features means that the severity of interference varied between the type of fluorescence camera used. More specifically, the observed interference with the OTS vicra completely obstructed fluorescence imaging with the PDE camera while its influence on the imaging output of the VITOM camera was only minor.…”
Section: Discussionsupporting
confidence: 66%
“…A surgical fluorescence phantom was fabricated for the experiments. This setup consisted of a previously described, siliconebased phantom 8 with two fluorescent beads incorporated (see Appendix B). In addition, surgically excised human tissue was used.…”
Section: Surgical Fluorescence Phantom and Human Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Next to the use of fully integrated hybrid detection modalities, hybrid surgical navigation concepts have been used to successfully integrate nuclear guidance (i.e. SPECT/CT or fhSPECT) with fluorescence guidance in vivo [175,[179][180][181]. In this approach, the surgical targets (e.g.…”
Section: Background and Recent Advances Fluorescencementioning
confidence: 99%